Epidemiology and care of individuals with cleft lip and palate in South Africa - Hlongwa, Phumzile (My University, 2019)
Background: Cleft lip and palate is amongst the five most common congenital anomalies reported in South Africa. Aim: In light of insufficient knowledge on cleft lip and palate, the aim of this PhD was to determine the prevalence of, and care provision to cleft lip with or without cleft palate individuals in South Africa. The specific objectives were to: describe the epidemiology of cleft lip and palate, analyse the current approach to care provision for individuals with cleft lip and palate, measure the interprofessional collaboration (IPC) among members of cleft lip and palate care team and determine the perceptions of and the support services available to caregivers of children with cleft lip and palate. Methods: A mixed methods, cross-sectional study was conducted at 11 specialised academic centres situated in six provinces of South Africa. The four distinct, but inter-linked components of this PhD study included:- a record review of cleft lip and palate data over a two-year period; a survey of cleft lip and palate leaders in 11 centres to determine the current approach to care provision for individuals with cleft lip and palate; a survey among cleft lip and palate team members to measure IPC; and the interviews with parents or caregivers on their perceptions of health service provision and support for their children with cleft lip and palate. STATA® 13 was used for quantitative data analysis, while the qualitative data was analysed using thematic content analysis. Results: The estimated prevalence of cleft lip and palate in the South African public sector was 0.3 per 1 000 live births, with provincial variation of 0.1/1000 to 1.2/1000. The distribution of clefts was: 35.3% cleft palate; 34.6% cleft lip and palate; and 19.0% cleft lip, with a statistically significant difference by gender. In the majority of centres the point of care for patients with cleft lip and palate was plastic surgery (9/11 centres = 81.8%). Surgical repair of the lip and palate (10/11 = 90.9%) and speech therapy (7/11 = 63.6%) dominated the type of treatment provided, highlighting gaps in the other types of treatment. Regarding the IPC, the domain of care expertise obtained the highest mean score of 2.92, whereas effective group function obtained the lowest mean score of 2.55. The category of health professional was the only factor that accounted for the differences in the overall IPC mean score. The mean age of caregivers was 33.3 years (range 17–68 years). Caregivers reported feelings of shock, anxiety, and sadness, exacerbated by the burden of care provision, and their experiences of health system deficiencies, lack of public awareness, and insufficient social support services. Conclusion: This PhD generated new knowledge on the epidemiology and care for individuals with cleft lip and palate in South Africa. A population-based surveillance system on congenital anomalies is necessary to collect relevant information, monitor trends and inform national policy. Strategies are needed to ensure the provision of a comprehensive package of essential services to individuals with cleft lip and palate, which will be enhanced with greater IPC. There should be greater involvement of caregivers in the treatment of their children, as well as public awareness campaigns on congenital anomalies
A thesis completed by published work Submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa 2019